Phospholipids of the Plasma Membrane – Regulators or Consequence of Cell Polarity? - Krahn, Michael P. (Frontiers in Cell and Developmental Biology, 2020)
Cell polarity is a key feature of many eukaryotic cells, including neurons, epithelia, endothelia and asymmetrically dividing stem cells. Apart from the specific localization of proteins to distinct domains of the plasma membrane, most of these cells exhibit an asymmetric distribution of phospholipids within the plasma membrane too. Notably, research over the last years has revealed that many known conserved regulators of apical-basal polarity in epithelial cells are capable of binding to phospholipids, which in turn regulate the localization and to some extent the function of these proteins. Conversely, phospholipid-modifying enzymes are recruited and controlled by polarity regulators, demonstrating an elaborated balance between asymmetrically localized proteins and phospholipids, which are enriched in certain (micro)domains of the plasma membrane. In this review, we will focus on our current understanding of apical-basal polarity and the implication of phospholipids within the plasma membrane during the cell polarization of epithelia and migrating cells.